120 P-MUC1C-ALLO1: An allogeneic car-t for multiple solid tumor indications. (9th November 2020) - Kozlowska, Anna; Zhang, Yan; Fritz, Jacqueline; Wang, Steven; Codde, Rebecca; Argus, Elvira; Ibitokou, Samad; Richardson, Vanitra; Jain, Sumiti; Richter, Maximilian; Patil, Deepak; Tan, Yening; et al.
Abstract : Background: MUC1 is a highly glycosylated protein that is expressed at the apical border of mucosal epithelium where it plays a protective role. MUC1 is comprised of an N-terminal subunit (MUC1N) tethered to a C-terminal subunit (MUC1C), forming a stable complex on the cell surface. A proteolytic 'stump' of MUC1C that may be aberrantly glycosylated is over-represented in cancer, making it an attractive therapeutic target. Here we report generation of allogeneic MUC1C-specific CAR T cells, P-MUC1C-ALLO1, that are designed to leverage the learnings of our P-BCMA-ALLO1 program. P-MUC1C-ALLO1 targets a MUC1C epitope and has the potential for efficacy against a wide range of solid tumors, without targeting normal epithelial cells. Methods mRNA-generated MUC1C CAR-T cells were evaluated for specificity and function by degranulation assay against various solid tumor and normal cells and cell lines. Autologous and allogeneic MUC1C CAR-T cells were produced using the piggyBac® DNA Modification System, a nonviral CAR-T manufacturing method that produces CAR-T products with an exceptionally high percentage of T stem cell memory (TSCM ) cells. To produce allogeneic cells, multiplex editing of both TRBC and B2M was performed with the Cas-CLOVER™ Site-Specific Gene Editing System to reduce or eliminate GvHD and host versus graft alloreactivity, respectively. To determine in vivo antitumor efficacy of MUC1C CAR-T cells, we employed the MDA.MB.468 triple negative breast cancer model and the OVCAR3 disseminated ovarian cancer model. Results: Specific degranulation of transiently-expressing CAR+ T cells was observed against multiple tumor cells, with no observable activity against normal human primary cells. In assay of stable P-MUC1C-101 CAR-T cells, more than 95% expressed CAR, and were comprised of an exceptionally high-percentage of TSCM cells (CD45RA+CD62L+CD45RO-). In vitro, P-MUC1C-ALLO1 cells specifically proliferated, lysed, and secreted IFN-γ against MUC1C+ breast and ovarian tumor cell lines. In breast cancer in vivo xenograft model, both unedited (MUC1C CAR-T) and edited (P-MUC1C-ALLO1) MUC1C CAR-T eliminated established, triple negative MDA.MB.468 tumor cells to undetectable levels, demonstrating the efficacy of the MUC1C CAR-T and the robustness of the allogeneic platform. In the OVCAR3 xenograft model, intraperitoneally administered MUC1C CAR-T eliminated established tumor cells to levels below the limit of detection. Conclusions: P-MUC1C-ALLO1 is Poseida's allogeneic CAR TSCM product that has a potential to treat multiple MUC1-expressing indications. P-MUC1C-ALLO1 displayed in vitro specificity for tumor vs normal cells, and in vivo efficacy against xenograft models of breast and ovarian cancer. We anticipate an IND filing and initiation of a Phase 1 clinical trial in 2021.